Leveraging Electronic Health Records and Administrative Datasets to Understand Social Determinants of Health: Opportunities and Challenges. (25th November 2019) - Tan, Jonathan; Wasey, Jack; Nelson, Olivia; Tam, Vicky; Simpao, Allan; Galvez, Jorge
No abstract available